Evolution of a Unified Strategy for Complex Sesterterpenoids: Progress toward Astellatol and the Total Synthesis of (−)‐Nitidasin. Issue 39 (20th August 2015) - Hog, Daniel T.; Huber, Florian M. E.; Jiménez‐Osés, Gonzalo; Mayer, Peter; Houk, Kendall N.; Trauner, Dirk
Abstract Astellatol and nitidasin belong to a subset of sesterterpenoids that share a sterically encumbered trans‐hydrindane motif with an isopropyl substituent. In addition, these natural products feature intriguing polycyclic ring systems, posing significant challenges for chemical synthesis. Herein, the evolution of our stereoselective strategy for isopropyl trans‐hydrindane sesterterpenoids is detailed. These endeavors included the synthesis of several building blocks, enabling studies toward all molecules of this terpenoid subclass, and of advanced intermediates of our initial route toward a biomimetic synthesis of astellatol. These findings provided the basis for a second‐generation and a third‐generation approach toward astellatol that eventually culminated in the enantioselective total synthesis of (−)‐nitidasin. In particular, a series of substrate‐controlled transformations to install the ten stereogenic centers of the target molecule was orchestrated and the carbocyclic backbone was forged in a convergent fashion. Furthermore, the progress toward the synthesis of astellatol is disclosed and insights into some observed yet unexpected diastereoselectivities by detailed quantum‐mechanical calculations are provided.